Interplay between noise-induced sensorineural hearing loss and hypertension: pathophysiological mechanisms and therapeutic prospects - Förster, Carola Y.; Shityakov, Sergey; Stavrakis, Stavros; Scheper, Verena; Lenarz, Thomas (Frontiers in Cellular Neuroscience, 2025)
More than 5% of the global population suffers from disabling hearing loss, primarily sensorineural hearing loss (SNHL). SNHL is often caused by factors such as vascular disorders, viral infections, ototoxic drugs, systemic inflammation, age-related labyrinthine membrane degeneration, and noise-induced hearing loss (NIHL). NIHL, in particular, leads to changes in blood-labyrinth-barrier (BLB) physiology, increased permeability, and various health issues, including cardiovascular disease, hypertension, diabetes, neurological disorders, and adverse reproductive outcomes. Recent advances in neuromodulation and vector-based approaches offer hope for overcoming biological barriers such as the BLB in the development of innovative treatments. Computational methods, including molecular docking, molecular dynamics simulations, QSAR/QSPR analysis with machine/deep learning algorithms, and network pharmacology, hold potential for identifying drug candidates and optimizing their interactions with BLB transporters, such as the glutamate transporter. This paper provides an overview of NIHL, focusing on its pathophysiology; its impact on membrane transporters, ion channels, and BLB structures; and associated symptoms, comorbidities, and emerging therapeutic approaches. Recent advancements in neuromodulation and vector-based strategies show great promise in overcoming biological barriers such as BLB, facilitating the development of innovative treatment options. The primary aim of this review is to examine NIHL in detail and explore its underlying mechanisms, physiological effects, and cutting-edge therapeutic strategies for its effective management and prevention.